FREQUENCY OF UNRECOGNISED DIABETIC RETINOPATHY AND NEPHROPATHY IN PATIENTS PRESENTING WITH DIABETIC FOOT ULCERS - Malik, Suleman Elahi; Ghaffar, Tahir; Ullah, Zafran; Kanwal, Shaista; Noor, Aqil; Aamir, azizul Hassan (Journal of Postgraduate Medical Institute, 2021)
Objectives: To determine the frequency of unrecognised diabetic retinopathy and diabetic nephropathy in patients presenting with diabetic foot ulcers. Methodology: This cross sectional study was conducted from November 2019 to May 2020. All patients presenting with diabetic foot ulcers were included in the study. Diabetic retinopathy was assessed by direct ophthalmoscopy followed by digital retinal camera imaging and diabetic nephropathy was assessed by 24 hours quantitative urinary proteins. Data was analysed with SPSS and presented in tables and graphs. Results: Among 104 patients 72 (69.2%) were male. Mean age for both genders was 53.29 ± 10.15 years (range: 33-75). Ninety eight (94.23%) had type 2 diabetes mellitus (T2DM) and 6 (5.76%) were having Type 1 diabetes mellitus (T1DM). The mean body mass index (BMI) was 26.98 ± 5.21 kg/m2 (range: 18.6-42.4) with mean duration of diabetes of 11.45 ± 5.08 years (range: 2-25). The mean HbA1C was 11.13 ± 2.19% (range: 6.6 to 17.5). Ninety two (88.46%) had unrecognised Diabetic retinopathy and 46 (44.23%) had unrecognised diabetic nephropathy. Forty four (42.30%) had both unrecognised diabetic nephropathy and retinopathy. Conclusions: High Percentage of unrecognised Diabetic retinopathy and nephropathy was found in the patients who presented with diabetic foot ulcers.